2008
DOI: 10.1021/pr800041d
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Time of Introduction of Cow Milk Protein to an Infant and Risk of Type-1 Diabetes Mellitus

Abstract: Several studies of infant feeding show a causal relationship between time of introduction of formula containing cow protein and risk of onset of type-1 diabetes mellitus. This paper cites the literature pro and con and discusses lipocalins which might play a role in the pathogensis. β Lactoglobulin, a major lipocalin protein in bovine milk, is homologous to the human protein glycodelin (PP14), a T cell modulator. Anti-β lactoglobulin cross-reacts with glycodelin. The newborn intestine does not have complete “c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Similar results were reported by Goldfarb [23] who suggested that Cow's milk products are associated with the onset of T1D. Also, this finding was in agreement with Megeid et al in Saudi Arabia [24], who found an association between T1DM and prolonged consumption of cow's milk (OR=4.3) and short duration of breastfeeding (OR=3.5).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were reported by Goldfarb [23] who suggested that Cow's milk products are associated with the onset of T1D. Also, this finding was in agreement with Megeid et al in Saudi Arabia [24], who found an association between T1DM and prolonged consumption of cow's milk (OR=4.3) and short duration of breastfeeding (OR=3.5).…”
Section: Discussionsupporting
confidence: 91%
“…The literature is still equivocal about the relationship of cow's milk products and the risk of type 1 diabetes, particularly the relationship between the time of their introduction to an infant and the onset of diabetes. Another review article [33] discussed this unsettled issue with several studies relating the age of introduction of dairy products to the risk of T1DM in particular when formula is introduced before 4 months of age, while other studies were not supporting this association. The same article added more evidence that cow's milk proteins trigger T1DM where antibodies to bovine beta-lactoglobulin were detected in the serum of children with diabetes while individuals without diabetes did not have this antibody [33].…”
Section: Discussionmentioning
confidence: 99%
“…Though many adults are hypothesised to have anti-IgG antibodies to cows' milk proteins, we are unaware of any previous study aimed at determining the prevalence of anti-b-LG antibodies in adults (Goldfarb, 2008). A study undertaken by Monetini et al (2002) found that people with latent autoimmune diabetes in adulthood (LADA) had higher values of antibodies to bovine beta casein than the control group, whereas people in the study with T2DM had lower values.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown an association between the time of introduction in the diet of proteins from cows' milk and the onset of type 1 diabetes mellitus (T1DM), though not all studies are in agreement (Goldfarb, 2008). A large caseecontrol study from Finland concluded that the age of introduction of dairy products is associated with the risk of T1DM (Virtanen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation